Кинематика Сверхкомплекса рассеянных звездных скоплений - Бархатова, К.А.; Нежинский, Е.М.; Осипков, Л.П. (Кинематика и физика небесных тел, 1990)
Кинематика Сверхкомплекса рассеянных звездных скоплений исследована методом Огородникова — Милна, примененным к пространственным скоростям скоплений (относительно квазикруговой скорости). Подтверждено вращение Сверхкомплекса с угловой скоростью ω = 1О±2 км·с⁻¹·кпк⁻¹. Выявлено его сжатие. The kinematics of the Supercomplex of open star clusters has been investigated by Ogorodnikov — Milne method applied to space velocities of clusters (relative to the quasi-circular velocity). The rotation of the Supercomplex with the angular velocity ω = 10±2 km·s⁻¹·kpc⁻¹ is confirmed. The contraction of the Supercluster is found.